Synthesis, Characterization and Biological Activity of Fe(II), Cu(II), and Cd(II) with Schiff Base Ligands (SBLs): Biological Screening of Divalent Metal Chelated Complex - Aslam, Muhammad; Noor, Khadija; Lateef , Mehreen; Noreen, Zahra; Javed, Muhammad Aneeq; Rehman, Mehvish Abdul; Habibullah, Khansa; Sohail, Aamir (Scientific Inquiry and Review, 2024)
This study aimed to develop novel Schiff base ligands (SBLs), namely N1,N2-Bis(4-nitrobenzylidene)benzene-1,2-diamine (1), 4,6-Dimethyl-N-((5-nitrofuran-2-yl)methylene)pyrimidin-2-amine (2) and N1,N2-Bis((5-nitrofuran-2-yl)methylene)benzene-1,2-diamine (3). It also aimed to examine how they coordinate with various bidentate transition metal ions to form metal complexes. The goal was to properly characterize the newly synthesized chemicals and investigate their possible uses in chemical and pharmaceutical industries, with an emphasis on the drug industry. Thin-layer chromatography (TLC) was used to methodically monitor and confirm the synthesis process at each step. The compounds were then put through characterization procedures such as Fourier transform infrared spectroscopy (FTIR), urease inhibition assays, and assessments of antioxidant activity.